1992
DOI: 10.1002/hlca.19920750327
|View full text |Cite
|
Sign up to set email alerts
|

Homolytic Substitution Reaction at a Silicon Atom

Abstract: Tris(trimethy1silyl)silane (2) is an efficient hydrosilylating agent of 1,6-dienes 1 operating via a free-radical chain mechanism. The intermediate alkyl radical 3 attacks the second olefinic bond of the diene 1 and forms cyclopentylalkyl radical 4. Using a low concentration of the hydrogen donor 2, a radical substitution reaction at the Si-center of cis-4 occurs and yields the bicyclic silane 6. The rate of this homolytic substitution at the Si-atom is 2.4 . lo5 s -~( S O O ) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 8 publications
0
28
0
3
Order By: Relevance
“…In addition, the cyclic silanes formed in these UMCT steps could be transformed into the corresponding alcohol derivatives by Tamao ± Fleming oxidation. [9] e) P. J. Dandliker, R. E. Holmlin, J. K. [6]). We suppose that the closest G is the initially oxidized base.…”
Section: S H I Reactions At Silicon As Unimolecular Chain Transfer Stmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, the cyclic silanes formed in these UMCT steps could be transformed into the corresponding alcohol derivatives by Tamao ± Fleming oxidation. [9] e) P. J. Dandliker, R. E. Holmlin, J. K. [6]). We suppose that the closest G is the initially oxidized base.…”
Section: S H I Reactions At Silicon As Unimolecular Chain Transfer Stmentioning
confidence: 97%
“…[11] Acidification after standard workup provided lactone 23, which was isolated in good yields (71, 72 %). (6) In summary, it has been shown that S H i reactions at silicon by C-centered radicals in g-position of stannylated silyl ethers are efficient UMCT reactions providing cyclic alkoxysilanes, which can easily be converted into the corresponding diol derivatives. In addition, excellent 1,2 stereoinduction was obtained in the cyclization reaction of chiral silyl ethers.…”
Section: S H I Reactions At Silicon As Unimolecular Chain Transfer Stmentioning
confidence: 99%
See 2 more Smart Citations
“…The first examples of cyclization reactions involving substitution at silicon were reported by Giese and coworkers 60 and Utimoto et al . 61 almost 20 years ago; these were included in the 1996 review.…”
Section: Homolytic Substitution At Siliconmentioning
confidence: 99%